ELLIPSIS DALAM FILM â€œOZ THE GREAT AND POWERFULâ€ KARYA SAM RAIMI - WENAS, TIFFANI DAYNE MARIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
Abstract The research entitled Ellipsis in Oz the Great and Powerful Movie by Sam Raimi. The objectives of this research are to identify, classify, and analyze descriptively the types of ellipsis in Oz the Great and Powerful movie. The writer conducted this research by using descriptive method. There are three steps to finish this research. First step is preparation, the writer watched the movie to find out the data. Second step is data collection, the writer collected all the sentences which contain ellipsis found in the movie and compared it with the movie script. Third step is data analysis, the writer identified and classified the sentences which contain ellipsis, then analyzed the data used theory of Aarts and Aarts (1982:89) The results of this research show that all of the types of ellipsis according to Aarts and Aarts (1982:89) were found in this movie. There are 56 sentences which contain ellipsis according to Aarts and Aarts (1982:89) found in this movie and they were classified into five types, those are: (1) Ellipsis involving the subject only total 4 sentences, (2) Ellipsis involving the subject and (part(s) of) the predicator total 34 sentences, (3) Ellipsis involving (part(s) of) the predicator total 3 sentences, (4) Ellipsis involving (part(s) of) the predicator and complement or adverbial total 7 sentences, (5) Ellipsis involving (part(s) of) the complement or adverbial total 8 sentences. Â  Keywords :Ellipsis, Movie: Oz the Great and Powerful, Aarts and Aarts.